Psychological Well-Being as a Mediator Between Physical and Sexual Health Among Rural Women in Wayanad, Kerala, India - Jasna V.R; Jerydananajane Eljo (PROGRESIF: Jurnal Dakwah, Sosial, dan Komunikasi, 2026)
Sexual health is an important component of women's overall well-being. However, in India, research on women's health continues to focus mainly on contraception, pregnancy, and infection control, while sexual well-being receives limited attention. Although physical and psychological factors are known to influence sexual health, few studies have examined these relationships together in rural Indian settings. To the best of our knowledge, this is among the first studies from rural Kerala to examine the mediating role of psychological well-being in the relationship between physical health and sexual health among women. Methods A cross-sectional community survey was conducted among 680 rural women in Wayanad district, Kerala. Data were collected using structured questionnaires measuring physical health, psychological well-being, and sexual health. Mediation analysis was performed using regression and bootstrapping techniques. Physical health significantly predicted both psychological well-being and sexual health. Psychological well-being also significantly predicted sexual health after controlling for physical health. Mediation analysis showed that psychological well-being partially mediated the relationship between physical health and sexual health (indirect effect = 0.039, 95% CI [0.019, 0.061]). The findings support the biopsychosocial perspective of women's sexual well-being. While better physical health contributes to improved sexual health, psychological well-being also plays an important mediating role. The results suggest that integrating psychological support into women's health services may help improve sexual well-being, particularly among rural women.